Bioethics In Neurospinal Patient Care - Andi Asadul Islam (Indoscholar, 2018)
Neurosurgery is among the newest of surgical disciplines, appearing in its modern incarnation at the dawn of twentieth century with the work of Harvey Cushing and contemporaries. Neurosurgical ethics involves challenges of manipulating anatomical locus of human identity and concerns of surgeons and patients who find themselves bound together in that venture. In recent years, neurosurgery ethics has taken on greater relevance as changes in society and technology have brought novel questions into sharp focus. Change of expanded armamentarium of techniques for interfacing with the human brain and spine — demand that we use philosophical reasoning to assess merits of technical innovations. Bioethics can be defined as systematic study of moral challenges in medicine, including moral vision, decisions, conduct, and policies related to medicine. Every surgeon should still take the Hippocratic Oath seriously and consider it a basic guide to follow good medical ethics in medical practice. It is simple and embodies three of the four modern bioethics principles – Respecting autonomy, beneficence, nonmaleficence, and justice. Spinal cord injury (SCI) is a devastating condition often affecting young and healthy individuals around the world. Currently, scientists are pressured on many fronts to develop an all-encompassing “cure” for paralysis. While scientific understanding of central nervous system (CNS) regeneration has advanced greatly in the past years, there are still many unknowns with regard to inducing successful regeneration. A more realistic approach is required if we are interested in improving the quality of life of a large proportion of the paralyzed population in a more expedient time frame.